Implementation of Kuntowijaya's Prophetic Values Towards Education of Boarding High School of Al Hikmah Batu - Muhith, Abdul; Batta, Usaila Raunaquel; Amelia, Ica; Sudesi, Abdul Rahman (Universitas Islam Sultan Agung, 2023)
An attempt to Islamize Kuntowijoyo's knowledge which contains three prophetic values consists of humanization to humanize human beings to achieve a situation called ‘Fitrah’ as well as education, liberation prevents the ‘munkar’ or forbidden, and transcendentization is one of the most important aspects, namely the divine aspect. The purpose of this study is to find out how the implementation and application of prophetic values in education at Al-Hikmah High School of Boarding School Batu, because prophetic values of it are very needed in a habit to do good things and stay away from things that are prohibited. The research is qualitative description in the pattern of field studies, data sources generated from primary sources obtained from interviews and secondary in the form of photos of activities, as well as books related to Kuntowijoyo's theory of thought. The activities implied by the three prophetic values of Kuntowijoyo such as the implementation of